Determinants of quality prostate cancer survivorship care across the primary and specialty care interface: Lessons from the Veterans Health Administration - Archana Radhakrishnan; Jennifer Henry; Kevin Zhu; Sarah T. Hawley; Brent K. Hollenbeck; Timothy Hofer; Daniela A. Wittmann; Anne E. Sales; Ted A. Skolarus (Cancer Medicine)
Abstract Background With over 3 million US prostate cancer survivors, ensuring high‐quality, coordinated cancer survivorship care is important. However, implementation of recommended team‐based cancer care has lagged, and determinants of quality care across primary and specialty care remain unclear. Guided by the theoretical domains framework (TDF), we explored multidisciplinary determinants of quality survivorship care in an integrated delivery system. Methods We conducted semistructured interviews with primary (4) and specialty (7) care providers across 6 Veterans Health Administration clinic sites. Using template analysis, we coded interview transcripts into the TDF, mapping statements to specific constructs within each domain. We assessed whether each construct was perceived a barrier or facilitator, examining results for both primary care providers (PCPs) and prostate cancer specialists. Results Cancer specialists and PCPs identified 2 primary TDF domains impacting their prostate cancer survivorship care: Knowledge and Environmental context and resources. Both groups noted knowledge (about survivorship care) and procedural knowledge (about how to deliver survivorship care) as positive determinants or facilitators, whereas resources/material resources (to deliver survivorship care) was noted as a negative determinant or barrier to care. Additional domains more commonly referenced by cancer specialists included Social/professional role and identity and Goals, while PCPs reported the domain Beliefs about capabilities as relevant. Conclusions We used the TDF to identify several behavioral domains acting as determinants of high‐quality, team‐based prostate cancer survivorship care. These results can inform prostate cancer survivorship care plan content, and may guide tailored, multidisciplinary implementation strategies to improve survivorship care across the primary and specialty care interface.